Investigating How Educational Interventions Can Promote Mental Health Awareness and Reduce Stigma - Nazeer, Atifa; Nazeer, Sidra; Fatima, Noreen; Akber, Rabia; Asghar, Anam; Asghar, Anfal; Attiq-Ur-Rehman, (Indus Journal of Bioscience Research, 2024)
Reducing stigma and helping people become aware of their mental health are fundamental means to promoting well being in society. Although mental health is recognized as increasingly important, stigma gets in the way of asking for help and of helping others. This paper examines the stochastic growth model featuring risky assets with uncorrelated returns, which can be described by matching functions. This research analyzes already existing literature and case studies that detect strategies, challenges, and outcomes of successful educational approaches. This study examines the degree to which educational interventions foster mental health awareness and decrease the stigma, in varied populations. We evaluate the impact of structured educational programs such as workshops, school based curricula, and community campaigns on participants' knowledge, attitudes and behavior pertaining to mental health using a mixed methods approach. I collected quantitative data through pre- and post-intervention surveys which show substantial improvements in mental health literacy and reductions on stigmatizing attitudes towards people Qualitative interviews regarding culturally tailored messaging, peer led discussions, and the fact that people have lived experiences and can use that to create that empathy and reduce prejudice likely further reinforce the importance of these factors. Results show that properly structured educational interventions broaden public knowledge about mental health problems and equip people with the ability to pursue help themselves or help others. This research has actionable insights for policymakers, educators, and health professionals in meeting the charge to address mental health stigma and building inclusive and supportive communities.